A Rogue by Compulsion: An Affair of the Secret Service - Bridges, Victor, 1878-1972 (Salt Lake City, UT : Project Gutenberg, 2003)
"A Rogue by Compulsion: An Affair of the Secret Service" by Victor Bridges is a novel written during the early 20th century. It follows the thrilling escape of Neil Lyndon, a convict from Dartmoor prison, who seizes a sudden opportunity to flee amidst chaos. This gripping tale delves into themes of freedom, survival, and the darker sides of human nature as Lyndon navigates his plight against a backdrop of dangerous circumstances and suspenseful intrigue. At the start of the story, the reader is introduced to Neil Lyndon, who is in the process of being herded back to prison when a fellow inmate's escape triggers a chaotic distraction. Seizing this fleeting moment of opportunity, Lyndon leaps into the woods and begins a desperate run for freedom, relying on his wits and physical prowess. As he traverses the treacherous terrain, he contemplates his past, grappling with memories of his trial and betrayal by his partner, George Marwood. Following a series of harrowing encounters, he reaches the sanctuary of a remote house, where he is unexpectedly met with both assistance and suspicion from its inhabitants, leading to further intrigue as he considers their intentions and the potential for revenge against those who wronged him. (This is an automatically generated summary.)
Release date is 2003-12-01
E-text prepared by Kevin Handy, Dave Maddock, Josephine Paolucci, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Spy stories; Secret service -- Fiction